2018
DOI: 10.4314/ljh.v29i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation challenges of social protection policies in four districts in Ghana: The case of the District Assembly Common Fund meant for Persons with Disabilities

Abstract: This study explores Ghana's implementation of a policy of two per cent of the District Assembly Common Fund (DACF) meant for persons with disabilities (PWDs) in four districts. It employed in-depth interviews with PWDs and offi cers in the District Assembly. The study revealed that the District Assemblies did not fully comply with directives from the central government to implement the policy. There were inconsistencies in the implementation of the policy and many PWDs received amounts that were less than they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…For instance, Agboga (2015) and Edusei et al (2017) reported that though beneficiaries were able to invest their share of the fund in business, education and the purchase of healthcare devices, they encountered several challenges to accessibility. For instance, despite the existence of the Disability Fund Management Committee (DFMC), they did not follow up to check whether beneficiaries have properly utilised their share of the fund (Adamtey et al, 2018; Okrah, 2016). Also, it has been reported that few persons with disabilities are able to access the grant, and that those who have benefitted were given little or fixed amounts, regardless of their needs (Okrah, 2016).…”
Section: Social Protection and Persons With Disabilitiesmentioning
confidence: 99%
“…For instance, Agboga (2015) and Edusei et al (2017) reported that though beneficiaries were able to invest their share of the fund in business, education and the purchase of healthcare devices, they encountered several challenges to accessibility. For instance, despite the existence of the Disability Fund Management Committee (DFMC), they did not follow up to check whether beneficiaries have properly utilised their share of the fund (Adamtey et al, 2018; Okrah, 2016). Also, it has been reported that few persons with disabilities are able to access the grant, and that those who have benefitted were given little or fixed amounts, regardless of their needs (Okrah, 2016).…”
Section: Social Protection and Persons With Disabilitiesmentioning
confidence: 99%
“…Sampling for other physical-chemical parameters was done on the sampling days described above. The pH of the compost (1:10 w/v waste: water extract), moisture, germination index, and Carbon dioxide emission during sampling days (mg CO2 g-1d-1) were done as described by [ 21 ]. Total Kjeldahl nitrogen (TKN) was analyzed using the Kjeldahl method.…”
Section: Methodsmentioning
confidence: 99%
“…Their research focused on members of OPDs in four districts of the Northern Region. A study by Adamtey et al, [ 28 ] found that the Disability Fund did not adhere to the fund guidelines. In some instances, beneficiaries received the same amounts of funds for different purposes.…”
Section: Introductionmentioning
confidence: 99%